Shiāghatu Manhaji Qism Ta’līm al-Lughah al-‘Arabiyyah bi Jāmi’ati Batu Sangkar al-Islāmiyyah al-Hukumiyyah wa ‘Alāqatihaa bi Manhaj al-Lughah al-‘Arabiyyah fī al-Madrasah al-Mutawasithah - Kamaluddin Kamaluddin; Ferki Ahmad Marlion; Muhammad Yusuf Salam; Yuri Choiratinnisa (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2022)
This research aims to describe how the approach to curriculum development of the Arabic language department at Batusankar State Islamic University, implementation of Arabic curricula in MTs / West Sumatra, relationship of the Arabic language curriculum of Batusankar State Islamic University with the achievement of the objectives of the Arabic curricula MTs / in West Sumatra. This research uses a qualitative design, with a multi-faceted approach to discuss the synchronization of the curricula of Arabic education departments with Arabic language teaching in MTs/ in West Sumatra and then obtaining this research data using documentation, observation and in-depth interview techniques. Then validate the data correctly, constraints by triangulating the data. The results showed that the curriculum of the Arabic language department at Batusankar State Islamic University is the result of "institutional union" respectively, not "structural union". The “institutional” results development model is called the grass-roots model with an academic subject approach. The Arab Curriculum Development Model for West Sumatra District Managers follows a “linear pillars” or “top-down” line of command procedure. The implementation plan for the implementation of the Arab curriculum for the Ministry of Foreign Affairs is implemented by Salbous and the Learning Implementation Plan (RPP) / preparation and implementation of a curriculum that cannot be separated. So that its maintenance is considered a unified unit. Then between the curriculum of the State Islamic University of Batusankar, the achievement of the objectives of the Arabic curricula, the MTs / middle school in West Sumatra has a relevant relationship.Keywords: approach to curriculum, curriculum of the Arabic language, The Arab Curriculum